Wave-driven flow induced by suspended and submerged canopies. (January 2019) - Chen, Haifei; Liu, Xiaofeng; Zou, Qing-Ping
Highlights: Negative wave-driven current jet at suspended and floating canopy bottom against wave direction. Positive wave-driven current generated at canopy top and maximum magnitude of current jet in good agreement with an empirical model. Current at canopy side interface is controlled by mixing layer. Good agreement between SWASH and two VOF-based CFD models waveFoam and ihFoam . Predicted wave attenuations compare well with analytical solutions. Abstract: Coastal canopies deliver a wide range of ecosystem services through the flow and transport processes within and around the canopies. This study presents a numerical investigation on the effect of suspended/floating canopies on wave-driven current around canopy using a non-hydrostatic model SWASH. The model results by SWASH for a submerged canopy are first validated with experiment measurements and compared with predictions from two Volume-of-Fluid (VOF) based free surface flow models. Then the effects of suspended/floating canopies on wave attenuation and vertical mean flow structures are examined using SWASH. The model results show that a strong shoreward wave-driven current is generated at the top of a suspended canopy in the same direction as the wave, same as that at the top of a benthic canopy. In contrast, a seaward mean current is generated at the bottom of a suspended canopy in the opposite direction to the wave. The predicted particle trajectories indicate that due to flow attenuation within canopy, at the bottom of the canopy, the fluid particles travel faster at the bottom half of their orbits outside the canopy in the opposite direction of wave propagation than at the top half of their orbits within the canopy in the direction of wave propagation. This leads to open particle orbits and a time‐averaged mean current in the opposite direction of wave propagation. The present study is the first attempt that reveals and examines this physical phenomena that would play an important role in particulate transport and exchange across the suspended canopies. The maximum magnitudes of wave induced currents at the top and bottom of canopy are consistent with a recent empirical formula extracted from the observations for submerged canopy. The predicted wave decay agrees well with a three-layer analytical solution for suspended and submerged canopy and indicates that the canopy vertical location plays an important role in wave attenuation and canopy induced currents. The spatial distribution patterns of the wave-driven current clearly support the notion that the current strength generated at the canopy interface is a function of horizontal oscillatory velocity, vertical orbital excursion and canopy density. The spanwise extent of the mean current is examined by a 3-D simulation where the canopy occupies only half the flume width. Numerical results show that the wave-driven current is mainly confined to the part of flume occupied by the canopy and that the current strength is soon attenuated to zero towards the other part of flume through a mixing-layer-like transition region at the canopy side interface.